The Immunoglobulin Superfamily Members syg-2 and syg-1 Regulate Neurite Development in C. elegans - Dana K. Tucker; Chloe S. Adams; Gauri Prasad; Brian D. Ackley (Journal of Developmental Biology, 2022)
Neurons form elaborate networks by guiding axons and dendrites to appropriate destinations. Neurites require information about the relative body axes during the initial projection from the cell body, and failure to receive or interpret those cues correctly can result in outgrowth errors. We identified a mutation in the Ig superfamily member syg-2 in a screen for animals with anterior/posterior (A/P) axon guidance defects. We found that syg-2 and its cognate Ig family member syg-1 appear to function in a linear genetic pathway to control the outgrowth of GABAergic axons. We determined that this pathway works in parallel to Wnt signaling. Specifically, mutations in syg-2 or syg-1 selectively affected the embryonically derived Dorsal D-type (DD) GABAergic neurons. We found no evidence that these mutations affected the Ventral D-type neurons (VD) that form later, during the first larval stage. In addition, mutations in syg-1 or syg-2 could result in the DD neurons forming multiple processes, becoming bipolar, rather than the expected pseudounipolar morphology. Given SYG-2′s essential function in synaptogenesis of the hermaphrodite-specific neurons (HSNs), we also examined DD neuron synapses in syg-2 mutants. We found syg-2 mutants had a decreased number of synapses formed, but synaptic morphology was largely normal. These results provide further evidence that the GABAergic motorneurons use multiple guidance pathways during development.